Implementation of the Scrum Methodology in Learning Chemistry to Improve Scientific Literacy: A Review - ., Nurlaila Hayati; Kadarohman, Asep; Sopandi, Wahyu; Abdulkadir Martoprawiro, Muhamad (KnE Social Sciences, 2024)
This study aimed to review the scientific articles published in international journals related to the scrum methodology and scientific literacy. In addition, the potential of implementing the scrum methodology in chemistry learning to improve scientific literacy is also discussed. This review used articles in Q1 and Q2 categories based on Scimago Journal & Country Rank data. Research data was collected by reviewing the articles with the following stages: determining the topic, searching the articles, identifying the main ideas, making an outline, and synthesizing the article review. The year of publication of the articles is limited from 2017 to 2021 to ensure the topic’s novelty. The research data were analyzed descriptively. The results showed that the scrum methodology could be implemented in chemistry learning. It focuses on student-centered learning. The context and examples used in the scrum methodology are a problem and phenomenon that occurs in everyday life, and components in the scrum methodology consist of sprints, roles, and artifacts. It was concluded that the scrum methodology can improve scientific literacy. Keywords: scrum methodology, scientific literacy, chemistry learning